Impact of the COVID-19 epidemic on the provision of pharmaceutical care in community pharmacies - Koster, Ellen S. (Res Social Adm Pharm, 2021)
BACKGROUND: Community pharmacists and their teams are easy accessible healthcare providers with an important role in primary care. As a consequence of the COVID-19 epidemic, (pharmaceutical) care and specifically communication between patients and healthcare providers is compromised. OBJECTIVE: To describe the impact of the COVID-19 epidemic on the provision of pharmaceutical care in the Netherlands. METHODS: A cross-sectional study with an online questionnaire was sent to community pharmacies in the Netherlands. The questionnaire covered the following main topics: changes in pharmacy setting and logistic procedures, communication about medication and baseline characteristics. RESULTS: Pharmacies implemented hygiene measures and minimized direct patient-provider contact, e.g. by delivering medication at home to a wider range of patients (47.0%), temporarily not conducting medication reviews (55.8%) and only performing inhalation instructions via telephone (22.3%). Only a small number of pharmacies used telepharmacy, such as video calling during patient education and counseling. A total of 76.7% of the participants expressed concerns towards the pharmaceutical care for vulnerable patients. CONCLUSIONS: Our results show considerable impact of the COVID-19 epidemic on both logistic procedures and services regarding patient education and counseling. Pharmacies should be stimulated to implement telepharmacy or remote service to optimally support patients during the COVID-19 epidemic.